Habilidades motoras orais e aspectos alimentares associados ao desenvolvimento de prematuros nos dois primeiros anos de vida - Vargas, Camila Lehnhart (2019)
The general objective of this research is to study the growth and development of preterm infants in the first two years of life, regarding the development of their oral motor skills and aspects of the feeding received. The study is longitudinal, descriptive and quantitative. The sample comprised 40 premature infants followed up at a hospital in the South of Brazil, between 2014 and 2018, in six moments: at birth and at four, six, twelve, eighteen and twenty-four months of age corrected for prematurity. The data of birth were collected in hospital records and the other moments, evaluated in the preterm follow-up outpatient clinic of the referred hospital. Anthropometric assessments of oral motor skills were performed with the Schedule for Oral Motor Assessment (SOMA) protocol, as well as of food consumption markers and developmental screening. Gestational age at birth averaged 32.47 (± 1.90) weeks and the mean weight was 1633.87 (± 467.53) grams. Most were female with adequate intrauterine growth. At four months, the mean corrected age was 3.37 (± 1.27) months. 82.5% had started being given complementary feeding and presented oral motor dysfunction, which progressed to normal during follow-up. Most premature infants were classified as eutrophic at different times. At 12 months, statistical significance was found between growth and oral motor function in the solid consistency, ie, children with normal oral motor function had better Z scores for weight for age, weight for height and body mass index for age compared to those with dysfunction (p≤0.05). Also, at twelve months of corrected age, consumption of ultra-processed foods and Z-scores of cephalic perimeter for age were higher in premature infants who did not consume these foods (p=0.001). Developmental screening by the Denver Test observed flaws in the four criteria evaluated (gross motor, fine motor, language and social behavior). Growth was monitored longitudinally during the first two years and a progressive pattern was observed when evaluating the evolution of means of weight, length and cephalic perimeter, and was considered adequate. Oral motor dysfunction was present in the majority of preterm infants at four months, when many were already receiving complementary feeding. From six months onwards, normal oral motor function was more frequent in the different consistencies, evolving during follow-up. There was a low prevalence of breastfeeding, even in a mixed form, at all times, with reduction during follow-up. The presence of processed and ultra-processed foods was elevated in the food routine since the six months of corrected age. The Denver test can be considered an easily applicable tool in the evaluation of children born prematurely. Knowing this population better, and the possible difficulties faced, observing the premature infant in aspects that involve the growth pattern, its oral motor skills, its food consumption pattern, as well as monitoring the global development, may favor the outpatient follow-up in the review of their conduct and protocols.